Efficacy and safety of combination therapies vs monotherapy of hypomethylating agents in accelerated or blast phase of Philadelphia negative myeloproliferative neoplasms: a systematic review and meta-analysis - Jia Chen; Kefei Wang; Zhijian Xiao; Zefeng Xu (Annals of Medicine, 2023)
AbstractBackground There is a lack of evidence regarding whether combination therapy of hypomethylating agents (HMAs) has better outcomes than HMA monotherapy in patients with Philadelphia chromosome-negative accelerated or blast phase myeloproliferative neoplasms (MPN-AP/BP).Materials and methods Pubmed, Embase, Web of Science and Cochrane library databases were searched for studies from inception of each database until 31 December 2021. Data extraction and synthesis were conducted following the PRISMA reporting guideline.Results It was found that HMAs plus venetoclax therapy yielded a higher CR/CRi rate than HMAs alone [36% vs 19%, p = .0204] and a higher CR rate than HMAs plus ruxolitinib [22% vs 8%, p = .0313]. HMAs plus ruxolitinib combination showed a higher ORR than HMA monotherapy [45% vs 30%, p = .0395], but there was no improvement in CR/CRi. The one-year and two-year OS rate for patients treated with HMAs plus venetoclx/ruxolitinib demonstrated a trend towards prolonged survival than HMAs alone [HMAs plus venetoclax: 24% vs 11%, p = .1295 and 12% vs 3%, p = .2357; HMAs plus ruxolitinib: 25% vs 11%, p = .0774 and 33% vs 3%, p = .051].Conclusion It was confirmed that HMA in combination with venetoclax is an effective and well-tolerated option in MPN-AP/BP patients in pre- as well as post-haematopoietic stem cell transplantation settings. HMA plus ruxolitinib therapy was revealed to be effective in patients with MPN-AP.Key MessagesCombination therapy with HMAs and venetoclax/ruxolitinib was associated with improved outcomes than HMAs alone in MPN-AP/BP patients.Further large-scale randomized controlled trials are needed to confirm regarding to the optimal treatment for this patient population.